2013
DOI: 10.1007/s10620-013-2632-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound and Magnetic Resonance Cholangiopancreatography in Patients with Idiopathic Acute Pancreatitis

Abstract: The combination of EUS and MRCP, when performed later after idiopathic acute pancreatitis, revealed 50 % of etiologies. The association of these two procedures and the subsequent follow-up reduced the rate of idiopathic pancreatitis by ~66 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 31 publications
2
53
1
3
Order By: Relevance
“…We and others have previously described cases of cannabis-related AP, but their frequency could be underestimated for many reasons [5,[14][15][16][17][18][19]: (i) the cases of toxic-induced AP being often difficult to prove; (ii) the difficulty in monitoring cannabinoids in the body and determining its pathophysiology as a cause of AP; (iii) the illegality of cannabis use and, consequently, patients not admitting usage.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We and others have previously described cases of cannabis-related AP, but their frequency could be underestimated for many reasons [5,[14][15][16][17][18][19]: (i) the cases of toxic-induced AP being often difficult to prove; (ii) the difficulty in monitoring cannabinoids in the body and determining its pathophysiology as a cause of AP; (iii) the illegality of cannabis use and, consequently, patients not admitting usage.…”
Section: Introductionmentioning
confidence: 94%
“…Other aetiologies (non-alcoholic, non-biliary AP) are less frequent; among these, the proportion of idiopathic AP has declined due to advances in radiological investigations and more detailed searches for autoimmune, drug-induced, or genetic causes [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent etiological factors are alcohol consumption and biliary stones as well as post-endoscopic retrograde cholangiopancreatography (post-ERCP), surgery, certain drugs, HIV infection, hyperlipidemia, and biliary anomalies. It is regarded as idiopathic acute pancreatitis when no causative factor is determined (4).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one study reported that the sensitivity of MRCP in the detection of choledocholithiasis decreases from 71 to 33 % as stone diameters fell below 6 mm [2]. Kondo et al corroborated this by stating that the performance of EUS was superior to loon dilation of the papilla performed, f followed by stone extraction using a biliary stone extraction balloon MRCP for detecting common bile duct stones < 5 mm in size [26,27]. There has been a debate whether the accuracy of MRCP for the detection of choledocholithiasis varies with ductal diameter.…”
Section: Where Do Eus and Mrcp Fit In With Ercp?mentioning
confidence: 98%
“…This review demonstrated that EUS was more sensitive and accurate than cholangiography in the detection of stones smaller than 4 mm. The diagnostic limitation of cholangiography in detecting small stones was partly explained by loss of sensitivity in dilated ducts [26,28,29]. EUS offers very high-resolution images (0.1 mm), thus allowing the detection of very small diameter stones [6].…”
Section: Where Do Eus and Mrcp Fit In With Ercp?mentioning
confidence: 99%